Analytical Hierarchy Process Algorithm for Traffic Sign Improvement Priority - Tamsir, Nurlindasari; Rosida, Vivi; Akhriana, Asmah; Intan, Indo; H.Umar, St. Amina (Program Studi Teknik Elektro Universitas Khairun, 2023)
Traffic signs are part of road equipment that is very important for motorists because they can provide direction while on the highway, and if there is damage, repair or replacement must be carried out immediately because it can cause traffic accidents. Data collection for damaged traffic signs is still done using the manual method, so it takes a long time. Therefore, a web- and android-based application was designed that implements the Analytical Hierarchy Process (AHP) algorithm in determining the priority of repair or replacement of traffic signs on the route of South Sulawesi Province. As a result of this research, the public can report the type of damage and its location via Android, and then the officer processes the data so that it displays the type of damage that is a priority for repair or replacement. Implement the Analytical Hierarchy Process algorithm into the application for prioritization of traffic sign improvement using two (two) web-based and Android platforms. System design using UML produces use cases (2 actors, admin, and user) and class diagrams (15 admin classes and 4 user classes). The black box used as a test produced 40 modules, of which all were in line with expectations